An analysis of the occupational safety legislation regime in the Malaysian construction industry - Rozanah Ab. Rahman (International Islamic University Malaysia, 2004)
The construction sector is one of the important sectors of the Malaysian economy since the rapid development of the sector has contributed towards the national economic growth and it provides economic opportunities for related industries and businesses. As the industry continues to progress, the problem of industrial accidents which causes social and economic problems to the nation is inevitable. This is evident from the industrial injury statistics which have shown an increase in the number of industrial accidents in the construction industry every year. For that reason, one of the causes or factors which give rise to the problem of accidents and fatalities at the construction sites has been identified due to the shortcomings of the legislation on occupational safety in the construction industry, viewed from its substantive adequacy and procedural compliance. Thus, in order to overcome the shortcomings, the safety legislation for the construction industry has been analyzed by the researcher, applying both the qualitative and quantitative methods. The qualitative method uses the traditional legal research methodology, comparative methodology, analytical and critical methodology, and the interview technique, while the quantitative method uses the survey technique. Consequently, the findings reveal that the shortcomings in the Factories and Machinery Act 1967 and the Occupational Safety and Health Act 1994 demand the legislation to be reviewed immediately; meanwhile, the 'Moderate' compliance of the legislation requires efforts to be taken to change the attitude and working culture in the industry without ado.